Best Laid Plans: How the Middle Class Make Residential Decisions Post-Disaster. (17th July 2021) - Rhodes, Anna; Besbris, Max
Abstract: Middle-class households typically search for housing with an eye to long-term residence and are able to maintain a high level of stability, but what happens when these households are forced to make mobility decisions after exposure to a disaster and subsequent residential displacement? Through longitudinal interviews with 59 households in a middle-class suburb of Houston that flooded during Hurricane Harvey, we found that residential mobility decisions—whether to stay and rebuild or move—were guided by households' durable plans about the future. The majority of households decided to remain and rebuild their homes, despite the ability to move and pressure from friends and family to relocate to less vulnerable places with similar amenities. The households that stayed had long-term plans to remain in their homes before the flood, while the small number who decided to move generally had well-defined plans to do so in the near future before the storm hit. Our findings reveal the role of plans in the residential decision-making of middle-class households and have implications for understanding post-disaster immobility at a time when middle-class households are increasingly exposed to environmental disasters.